KEBERAGAMAN GENDER DALAM DEWAN DIREKSI DAN KINERJA PERUSAHAAN PERSPEKTIF CRITICAL MASS: SCOPING REVIEW - Nur Diana Kholidah SM; Bambang Sugeng; Puji Handayati (Jurnal Manajemen, Ekonomi dan Akutansi (JUMEA), 2026)
Research on gender diversity in boards of directors and company performance shows diverse empirical findings and has yet to reach a consensus. Some studies report a positive influence, while other studies find a negative, insignificant, or non-linear relationship. These conditions indicate that the relationship between gender diversity and company performance is complex and cannot be adequately explained through a linear approach. This study aims to map and synthesize academic literature discussing this relationship through a scoping review approach. The research method refers to the Arksey and O'Malley (2005) framework, which includes the stages of identifying research questions, literature searches, article selection, data mapping, and summarizing and reporting results. The search was conducted in reputable international journal databases covering publications from the last fifteen years. Based on the selection process, ten relevant empirical articles were obtained and analyzed systematically. The results of the scoping review show that the relationship between gender diversity on the board of directors and company performance is dominated by nonlinear patterns, particularly inverted U-shaped and U-shaped patterns. Some studies in the literature identify a threshold or critical mass of female representation, generally in the range of 30-40 percent, at which the contribution of gender diversity to company performance begins to be more substantial. This study contributes by presenting a comprehensive conceptual and empirical mapping of research developments on gender diversity and company performance, as well as identifying relevant research gaps for further research development.